Hubungan Antara Efikasi Diri Dan Kesadaran Metakognitif Dengan Kesiapan Kerja Mahasiswa Tingkat Akhir - Reza Bagus Prakoso; Dewi Lutfianawati; Supriyati (Nathiqiyyah, 2025)
Final-year university students are in the early adulthood phase, facing developmental tasks such as establishing independence, pursuing careers, and preparing to enter the workforce. Challenges like high unemployment rates, skills mismatch with labor market demands, and intense competition are associated with their work readiness. This study aims to examine the relationship between self-efficacy and metacognitive awareness with work readiness among final-year students in Bandar Lampung. The research method uses a quantitative approach with multiple linear regression analysis techniques. The research involved 167 participants from various study programs in Malahayati University, selected through convenience sampling. Results indicate that most subjects demonstrated moderate work readiness levels. Data analysis revealed: (3) collectively, self-efficacy and metacognitive awareness showed significant relationship with work readiness; (2) a significant positive relationship between self-efficacy and work readiness; and (3) no significant relationship between metacognitive awareness and work readiness. These findings suggest that self-efficacy serves as a key factor in work readiness, while metacognitive awareness provides supplementary support despite lacking independent influence. Keywords : Work Readiness, Self-Efficacy, Metacognitive Awareness Final-year university students are in the early adulthood phase, facing developmental tasks such as establishing independence, pursuing careers, and preparing to enter the workforce. Challenges like high unemployment rates, skills mismatch with labor market demands, and intense competition are associated with their work readiness. This study aims to examine the relationship between self-efficacy and metacognitive awareness with work readiness among final-year students in Bandar Lampung. The research method uses a quantitative approach with multiple linear regression analysis techniques. The research involved 167 participants from various study programs in Malahayati University, selected through convenience sampling. Results indicate that most subjects demonstrated moderate work readiness levels. Data analysis revealed: (3) collectively, self-efficacy and metacognitive awareness showed significant relationship with work readiness; (2) a significant positive relationship between self-efficacy and work readiness; and (3) no significant relationship between metacognitive awareness and work readiness. These findings suggest that self-efficacy serves as a key factor in work readiness, while metacognitive awareness provides supplementary support despite lacking independent influence. Keywords : Work Readiness, Self-Efficacy, Metacognitive Awareness